Next-Generation mRNA Vaccines: Applications Beyond COVID-19 - Rohit Saroha; Gauri Mudgal; Muneeb Kosvi; Prabha Kumari (International Journal of Vaccines, 2026)
Messenger RNA (mRNA) vaccine technology has become a paradigm shift in contemporary medicine and, with remarkable success in the COVID-19 pandemic, has opened the door to a new wave of vaccines development. In contrast to the traditional vaccine methods, mRNA vaccines are based on the synthetic genetic code that allows host cells to express target antigens, thus eliciting strong humoral and cellular immunity. The speed of development, efficacy, scalability of manufacture, and flexibility of mRNA vaccines have led to increased interest in their uses outside of prevention of infectious diseases. This review gives an in-depth insight into next-generation mRNA vaccine platforms such as self-amplifying RNA (saRNA), circular RNA (circRNA), personalized mRNA vaccines, and improved lipid nanoparticle delivery systems. Recent developments in vaccine engineering have enhanced stability, immunogenicity and delivery efficiency and overcome some of the shortcomings of first-generation mRNA vaccines. Moreover, the growing use of mRNA in cancer immunotherapy, influenza, respiratory syncytial virus, human immunodeficiency virus, antimicrobial resistance, autoimmune diseases, and genetic diseases indicates that the technology is flexible to use as a preventive and therapeutic platform. It also addresses the current clinical trials, new regulatory approvals, and new technologies in vaccine delivery, which are catalyzing the next wave of mRNA vaccine development. Even with tremendous improvements, issues of storage needs, production expenses, quality control, legal routes and accessibility around the world are critical issues. The future outlooks of artificial intelligence-aided vaccine design, the creation of universal vaccines, responding to pandemics, and precision vaccinology would further increase the effect of mRNA-based therapeutics. Altogether, next-generation mRNA vaccines are a promising and fast-developing solution that has the potential to transform healthcare in the world as it will provide the opportunity to prevent and treat diseases much faster, safer, and more personally
Keywords: mRNA vaccines; personalized vaccines; precision vaccinology; self-amplifying RNA; vaccine delivery systems